Pharmacology in special populations: extreme age - B. K. Romanov; S. K. Zyryanov (Izdatelstvo OKI, 2019)
The article deals the definition, history of development in Russia, the main provisions, problems and prospects of development of pharmacology of extreme ages. The features of the nomenclature of medicines and the applicability of different dosage forms in different age periods are shown. Recommendations on rational use of medicines in patients of special populations - extreme ages are given. The risks of responsible self-treatment and polypharmacology are indicated. The data of international monitoring of drug safety in patients of extreme ages are presented. The article is addressed to pharmacologists, clinical pharmacologists, drug developers and doctors of medical specialties.